Acceptability in Marjana Moškrič’s Novel Sneg - Krajnc Ivič, Mira (Trideset let literarne nagrade večernica, 2026)
The article examines acceptability in Marjana Moškrič’s young adult dystopian novel Sneg. As a primary text-external feature of functionality, acceptability depends on the addressee’s interpretation, shaped by their knowledge and goals, the communicative situation, and the relationship between the participants. A qualitative analysis of five excerpts combines text-linguistic, pragmatic, conversation-analytic, and discourse-analytical approaches. The analysis shows that disagreement over content does not in itself entail unacceptability; this arises when the addressee does not accept the interlocutor’s turn as relevant and thus fails to ratify the utterance in the function in which it was offered. In peer and protectively oriented asymmetric relationships, disagreement, topic shifts, the flouting of cooperative maxims, or apparent non-observance of politeness do not prevent the conversation from continuing. In hierarchical family or institutionally repressive relationships, rejecting what is verbalised as relevant restricts or terminates communication. Through its dialogues, the novel thus contributes to the construction of a dystopian social order.